2022
DOI: 10.1101/2022.01.19.22269524
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Psychological flexibility and the moderating role of the therapeutic working alliance in Acceptance and Commitment Therapy in Daily Life (ACT-DL) in an early psychosis sample

Abstract: Background: We investigated treatment effects of Acceptance and Commitment Therapy in Daily Life (ACT-DL) on psychological flexibility (PF) and the moderating role of the therapeutic working alliance on these effects in patients with early psychosis. Methods: ACT-DL is an ecological momentary intervention (EMI) combining face-to-face ACT with a smartphone app. In the multi-center INTERACT randomized controlled trial, n=148 early psychosis individuals were randomized to either treatment as usual (TAU as the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…In a randomized controlled trial, we found that ACT-DL was outperforming treatment-as-usual (including CBT) in improving negative symptoms and social functioning, two of the hardest-to-treat symptoms (12). Furthermore, we found that the intervention was feasible and accessible although it could further be optimized for use in this patient group (13).…”
Section: Guest Editorialmentioning
confidence: 91%
“…In a randomized controlled trial, we found that ACT-DL was outperforming treatment-as-usual (including CBT) in improving negative symptoms and social functioning, two of the hardest-to-treat symptoms (12). Furthermore, we found that the intervention was feasible and accessible although it could further be optimized for use in this patient group (13).…”
Section: Guest Editorialmentioning
confidence: 91%
“…This would avoid focusing on mechanisms that mirror the skills themselves, for example, acceptance and mindfulness exercises improving acceptance and mindfulness skills (Johannsen et al, 2022). The use of non‐self‐report measures can also help to understand how ACT skills lead to psychological flexibility, for example, experimental lab tasks, wearable devices and ecological momentary assessment across contexts of ACT skill use and time‐lagged physiological, cognitive and behavioural responses (e.g., Van Aubel et al, 2022; Van der Gucht et al, 2019).…”
Section: Lingering Questionsmentioning
confidence: 99%
“…Browne et al (2021) found that engagement (i.e., number of interactions) with an ACT smoking cessation smartphone app in people with severe mental illness including psychosis mediated the effect of the intervention on decreased number of cigarettes smoked per day compared with a non-ACT smoking cessation app. A recent multi-centre RCT of ACTp combined with ecological momentary intervention versus treatment as usual in people with early psychosis found that 'momentary openness' improved more in ACTp and higher client-rated working alliance moderated (improved) this outcome (Van Aubel et al, 2022).…”
Section: Potential Mechanisms and Moderators Of Effectsmentioning
confidence: 99%